Volume 7B: Ocean Engineering 2018
DOI: 10.1115/omae2018-78209
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hydrophobic Painting in Model-Scale Marine Propeller

Abstract: This paper aims to perform a numerical analysis of application effects of a superhydrophobic paint by completely coating the blades of a model-scale marine propeller in order to make it a superhydrophobic surface (SHS). First, a two-dimensional study was conducted. Two foils were analyzed for several hydrophobic conditions, varying the slip length. Pressure and skin friction distributions were shown. There is an increase of lift-to-drag ratio with hydrophobicity, but followed by an increase in suction pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…With a defined method for propeller simulation, a numerical analysis based on RANS CFD software is done to study the behavior of the boundary layer flow with the condition that imposes the low-friction / hydrophobic effect in a fully-covered super-hydrophobic propeller (Katsuno et al, 2018). This section aims to estimate the gain of performance in propellers, guiding the definitions and restrictions that should be looked for the topology optimization.…”
Section: Results Of Hydrophobic Simulationsmentioning
confidence: 99%
“…With a defined method for propeller simulation, a numerical analysis based on RANS CFD software is done to study the behavior of the boundary layer flow with the condition that imposes the low-friction / hydrophobic effect in a fully-covered super-hydrophobic propeller (Katsuno et al, 2018). This section aims to estimate the gain of performance in propellers, guiding the definitions and restrictions that should be looked for the topology optimization.…”
Section: Results Of Hydrophobic Simulationsmentioning
confidence: 99%
“…Choi et al [18] used a commercial super-hydrophobic coating on the surface of a 42 mm diameter double-blade propeller and found that the super-hydrophobic coating could reduce the turbulent kinetic energy of the propeller's wake by about 20%. Katsuno et al [19] conducted CFD research on a super-hydrophobic coated propeller and used the concept of boundary layer slip length to simulate the effect of hydrophobic slip. The results showed that the propeller efficiency calculated by this boundary layer hydrophobic model did not increase significantly.…”
Section: Introductionmentioning
confidence: 99%
“…The objective is to analyze the trade-off between the skin-friction drag reduction due to SHS presence, an expected result, and the increase of suction pressure, i.e., reduction of absolute pressure, which may increase the cavitation phenomena. This chapter, published in Katsuno, Dantas and Silva (2018), aims to estimate the gain of performance in propellers, guiding the definitions and restrictions that should be looked for topology optimization, as well as being necessary for a correct definition for the cost function.…”
Section: Experimental Values Comparative and Discussionmentioning
confidence: 99%